IMPACT DE TAUX DE CHANGE SUR L’INDICE NATIONAL DE PRIX A LA CONSOMMATION DES MENAGES EN RDC DE 2001 – 2016 - Benjamin , AKEMANI AWENDE (IJRDO - Journal of Business Management, 2021)
Price stability at the national level is one of the monetary policy objectives of the Monetary Authority in the RD. Congo, which is going through the maintenance of inflation rates to such a low level. The RD. Congo, a post-conflict country with a low income fails to stabilize the long-term price; that is why the Congolese household is confronted with the cost of living and the inevitable change in prices. This change in prices is influenced by the fluctuation of exchange rates often on the rise, the Congolese franc depreciates against the US dollar which has a negative effect on the household budget. The exchange rate significantly influences the price in the market for good and service.